Evaluation of glycosylated docetaxel-encapsulated liposomes prepared by remote loading under solubility gradient. (17th February 2016) - Shigehiro, Tsukasa; Zhai, Wenjia; Vaidyanath, Arun; Masuda, Junko; Mizutani, Akifumi; Kasai, Tomonari; Murakami, Hiroshi; Hamada, Hiroki; Salomon, David S.; Mikuni, Katsuhiko; Seno, Yuhki; Mandai, Tadakatsu; et al.
Abstract: Docetaxel comprises one of the most effective anti-cancer drugs despite of serious side effects. Liposomes encapsulation is practically feasible to deliver the drug. However, due to the significant hydrophobicity, docetaxel will be integrated into the lipid bilayer resulting in poor encapsulation capacity. Here, we evaluated a remote loading strategy using a solubility gradient made between the two solvents for 7-glucosyloxyacetyldocetaxel, which has enhanced water solubility of docetaxel with a coupled glucose moiety. Therefore, 7-glucosyloxyacetyldocetaxel was more effectively encapsulated into liposomes with 71.0% of encapsulation efficiency than docetaxel. While 7-glucosyloxyacetyldocetaxel exhibited 90.9% of tubulin stabilisation activity of docetaxel, 7-glucosyloxyacetyldocetaxel encapsulated in liposomes significantly inhibited the growth of tumour in vivo with side effects less than unencapsulated drug. Collectively, the encapsulation of 7-glucosyloxyacetyldocetaxel into liposomes by remote loading under the solubility gradient is considered to be a promising application to prepare practical drug delivery system.